2014
DOI: 10.1120/jacmp.v15i4.4831
|View full text |Cite
|
Sign up to set email alerts
|

Design and production of 3D printed bolus for electron radiation therapy

Abstract: This is a proof‐of‐concept study demonstrating the capacity for modulated electron radiation therapy (MERT) dose distributions using 3D printed bolus. Previous reports have involved bolus design using an electron pencil beam model and fabrication using a milling machine. In this study, an in‐house algorithm is presented that optimizes the dose distribution with regard to dose coverage, conformity, and homogeneity within the planning target volume (PTV). The algorithm takes advantage of a commercial electron Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0
4

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(134 citation statements)
references
References 24 publications
1
129
0
4
Order By: Relevance
“…This paper showed that a 3D printed bolus represented a precise reproduction of the designed model bolus at relatively low cost. This precision increased the certainty that the dose distribution in the target area would be consistent with the planned dose distribution and results a substantial reduction of the volume of normal tissues being irradiated, which agrees with the results of Su et al (10) . The 3D printed bolus displayed a better it to the planned model and greater material uniformity compared to the classical paraf in bolus.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…This paper showed that a 3D printed bolus represented a precise reproduction of the designed model bolus at relatively low cost. This precision increased the certainty that the dose distribution in the target area would be consistent with the planned dose distribution and results a substantial reduction of the volume of normal tissues being irradiated, which agrees with the results of Su et al (10) . The 3D printed bolus displayed a better it to the planned model and greater material uniformity compared to the classical paraf in bolus.…”
Section: Discussionsupporting
confidence: 82%
“…Using 3D printed bolus could help to overcome the problem with air cavities and improve the quality of realized treatment, by reproducibility of daily setup conditions on irregular surfaces, which was con irmed by Shin -Wook et al (11) . Additionally, a 3D printer can be easily installed in the cancer center and offer practical advantages -neither patient nor staff needs to be present all the time during the bolus production, which was con irmed by Su et al (10) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical sites for which bolus ECT is useful are well documented in the literature, e.g. posterior wall sarcomas 25 , postmastectomy chest wall 2628 , head and neck 29,30 , and extremities 31 , and on the .decimal web site.…”
Section: Discussionmentioning
confidence: 99%